Hebrew as a Subject of Research and Teaching in Poland from the Early 16th Century to the 20th Century. A Contribution to Further Reflections - Marcinkowski, Roman (Verbum Vitae, 2023)
The paper explores the history of Hebrew studies in Poland from the early 16th century to the 20th century. The beginnings of academic studies and thorough research into biblical Hebrew can be traced back to the 16th century as the first lecturers of classical languages appeared at the Kraków University. They were also the first to write textbooks for learning this language, and some of tchem translated biblical books from their original languages. Jewish printing houses had a significant impact on the growing interest in Hebrew studies, both in the Jewish and Christian communities. Passion for Hebrew was still observed in Poland in the 17th and 18th centuries. In turn, the late 18th century and the 19th century were the times of the Jewish Enlightenment (Haskalah) and disputes about the shape of Hebrew. At universities theological studies included biblical Hebrew courses. The 20th century saw the emergence of numerous centres for Hebrew studies at leading Polish universities, offering full-time Bachelor and Master’s programmes, conducting interdisciplinary research, developing scholarly publications in the field and establishing organizations aiming to promote research on Jewish history, culture and language.